Utilizing Storytelling to Instill Positive Values in Children in Aek Muara Pinang Village - Arifin Hutabarat; Tesa Lonika; Hestina Putri Lumbangaol; Grace Simamora; Herfian Warnares; Melina Sipahutar (International Journal of Educational Practice and Policy, 2025)
This study aims to determine the effectiveness of the use of storytelling methods in instilling good values ​​in children in Aek Muara Pinang Village. This activity was carried out by KPPM students of the Religious Extension Education Study Program through the formation of child foster groups who routinely attend spiritual service sessions. One of the materials used in storytelling is the Bible story of David and Goliath. This study uses a qualitative approach with data collection techniques in the form of participant observation, interviews, and documentation. Data analysis techniques are carried out by means of data reduction, data presentation and drawing conclusions. The results of the study showed that the storytelling method proved effective in building children's understanding of good values ​​such as loving each other, helping each other, and obedience to parents. The children showed high enthusiasm for the stories told, and consistently began to show behavioral changes in everyday life. This study suggests that the storytelling method be applied more widely as a tool for children's spiritual education in Christian communities, especially in areas with limited access to formal character education.